2016
DOI: 10.18203/2394-6040.ijcmph20160643
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge, practices and treatment seeking behaviour among diabetic patients

Abstract: The world prevalence of diabetes among adults (aged 20-79 years) will be 6.4%, affecting 285 million adults, in 2010, and will increase to 7.7% and 439 million adults by 2030. Between 2010 and 2030, there will be a 69% ABSTRACT Background: Adherence is a complex process and patients' decisions about how to manage their medications are likely based on economic, physical, psychological, and social considerations. Identifying factors associated with adherence would be of value for family physicians in focusing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Similar findings were reflected in a study by Sawant et al where awareness of hypoglycemia was found to be 56.3%. [9] Only 22.6% of the study subjects were aware of the complications of diabetes, and among them, more than 50% were aware of ocular complications and 43.1% knew about renal complications and delayed healing of wound. Similar findings were reflected in a study by Murugesan et al in the urban population of South India where only <30% of the subjects were aware of renal, ocular, and neurological complications.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar findings were reflected in a study by Sawant et al where awareness of hypoglycemia was found to be 56.3%. [9] Only 22.6% of the study subjects were aware of the complications of diabetes, and among them, more than 50% were aware of ocular complications and 43.1% knew about renal complications and delayed healing of wound. Similar findings were reflected in a study by Murugesan et al in the urban population of South India where only <30% of the subjects were aware of renal, ocular, and neurological complications.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that there is still an inadequate awareness about various aspects of diabetes among the general public and also there is also a lack of knowledge and awareness about the existing interventions in prevention and management of its complications. [8,9] Hence, with this background, the current study was conducted with an objective to assess the awareness of Type 2 DM among the general population and diabetics residing in the rural area of Mangalore, South India.…”
Section: Introductionmentioning
confidence: 99%
“…Raising the awareness of the population will also contribute to acceptable health seeking behaviours [ 45 ]. Participants pointed out that people in the community do not read much, unsurprisingly because most are not highly educated; they are more attracted to plays on television.…”
Section: Discussionmentioning
confidence: 99%